CONTRIBUTION TO THE KNOWLEDGE OF SOME PHYTOPHAGUS MITES FOUND IN THE YUCCA CULTIVATION Manihot esculenta Crantz, IN COLOMBIA - GUERRERO, JOSÉ MARÍA; BELLOTTI, ANTHONY C. (Revista Colombiana de Entomología, 1980)
In 1973, the International Center of Tropical Agriculture initiated research on mites attacking cassava, Manihot esculenta Crantz. The results of this research to date has identified 16 mite species attacking cassava in Colombia. The most common cassava mites found in Colombia that may cause economic yield losses are Mononychellus tanajoa, M. caribbeanae, Tetranychus urticae, T. cinnabarinus and Oligonychus peruvianus. The remaining species do not have economic importance in cassava owing to their occasional presence.